Response surface optimization of the cacao criollo fermentation process in the province of Utcubamba, Amazonas-Peru - Mori Mestanza, Diner; Barrena Gurbillón, Miguel; Oliva Cruz, Segundo; Chavez Quintana, Segundo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The fermentation process of native fine aroma cacao criollo (Theobroma cacao) in the province of Utcubamba, Amazonas, Peru, was optimized. A Box-Behnken statistical design was applied, whose factors were inoculum concentration, fermentation time and inoculation sequence. With the optimized model, a phenolic content of 12.99 mg AGE.g-1 cocoa, a fermentation index of 1.05, and theobromine and caffeine contents of 4.89.100 g-1 cocoa and 1.81.100g-1 cocoa, respectively, were obtained. Additionally, with a panel of nine certified and accredited tasters, the basic and special descriptive qualitative sensory attributes of the fermented and dry cocoa beans were determined, obtaining a maximum quality score of 71.1, and the sensory descriptors floral, fruity, nutty, sweet, bitter, acidity and adequate astringency were identified. In the cocoa obtained with the best treatment, 64 volatile compounds from the families of aldehydes, ketones, alcohols, esters, acids and pyrazines were identified by gas chromatography coupled to a mass detector with solid-phase microextraction (GC-MS-SPME-HS). In conclusion, it was possible to optimize the fermentation process of cacao criollo to obtain cocoa with high functional and sensory properties.